Checkpoint signaling and error correction require regulation of the MPS1 T-loop by PP2A-B56 - Hayward, D; Bancroft, J; Mangat, D; Alfonso-Pérez, T; Dugdale, S; McCarthy, J; Barr, FA; Gruneberg, U (Rockefeller University Press, 2019)
During mitosis, the formation of microtubule–kinetochore attachments is monitored by the serine/threonine kinase monopolar spindle 1 (MPS1). MPS1 is recruited to unattached kinetochores where it phosphorylates KNL1, BUB1, and MAD1 to initiate the spindle assembly checkpoint. This arrests the cell cycle until all kinetochores have been stably captured by microtubules. MPS1 also contributes to the error correction process rectifying incorrect kinetochore attachments. MPS1 activity at kinetochores requires autophosphorylation at multiple sites including threonine 676 in the activation segment or “T-loop.” We now demonstrate that the BUBR1-bound pool of PP2A-B56 regulates MPS1 T-loop autophosphorylation and hence activation status in mammalian cells. Overriding this regulation using phosphomimetic mutations in the MPS1 T-loop to generate a constitutively active kinase results in a prolonged mitotic arrest with continuous turnover of microtubule–kinetochore attachments. Dynamic regulation of MPS1 catalytic activity by kinetochore-localized PP2A-B56 is thus critical for controlled MPS1 activity and timely cell cycle progression.